Hierarchical Inter-Object Traces for Specification Mining - LO, David (Institutional Knowledge at Singapore Management University, 2008)
Major challenges of dynamic analysis approaches to specification mining include scalability over long traces as well as comprehensibility and expressivity of results. We present a novel use of object hierarchies over inter-object traces as an abstraction/refinement mechanism enabling scalable, incremental, top-down mining of scenario-based specifications.